The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1021/ie3023912
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Microcapsules Deposited in Cotton Fabrics before and after Abrasion Using Fluorescence Microscopy

Abstract: Perfume microcapsules for laundry applications are extensively used in home and consumer care products. Capsules have to bind into the fabric during washing and survive the rinsing and drying steps until the desired moment of rupture, usually when in contact with the skin. In order to assess the performance of the microcapsules in the different steps, quantification methods are required. It is reported here the first methodology, using fluorescence microscopy, whereby the number and size of fluorescent microca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Moreover, the spectral characteristics of core materials can also be utilized to analyze their release properties. For example, Ruben et al [18] observed the crushing and residual property of prepared fluorescent dye microcapsules in finished fabric with a fluorescence microscope, and Bezerra et al [19] evaluated the controlled-release mechanism of citronella oil microcapsules in different substrates with an attenuated total reflection FTIR spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the spectral characteristics of core materials can also be utilized to analyze their release properties. For example, Ruben et al [18] observed the crushing and residual property of prepared fluorescent dye microcapsules in finished fabric with a fluorescence microscope, and Bezerra et al [19] evaluated the controlled-release mechanism of citronella oil microcapsules in different substrates with an attenuated total reflection FTIR spectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…21 Controlled release can furthermore take place continuously The release profile of MCs is generally determined by dispersing of the particles in a solution and by measuring the evolution of the solute concentration over time. The release kinetics can be determined by a range of techniques adapted to the core content, such as spectroscopic techniques (UV-vis, 141 NMR, FTIR spectroscopic methods), microscopy (fluorescence), 142,143 chromatography (GC, 114,144 HPLC 145 ), sensors (e-nose 146 ) and TGA. Indirect measurements can also be performed by measuring the effect of the released core materials (e.g., cytotoxicity) 147 .…”
Section: Colloidal Propertiesmentioning
confidence: 99%
“…The amphiphilic molecules used in these conditioners are double-chain surfactants that self-assemble in vesicles [ 10 , 11 , 12 , 13 ]. The vesicles have a dual role: they provide long-term stability and transport active ingredients such as oils [ 14 ] and fragrance capsules [ 15 , 16 ] onto the fibers. Throughout the history of softeners, surfactants have been replaced by more effective and less toxic ones [ 8 ].…”
Section: Introductionmentioning
confidence: 99%